Protein tyrosine phosphatase hPTPN20a is targeted to sites of actin polymerization - Fodero-Tavoletti, Michelle T. (Portland Press Ltd., 2005)
The human genome encodes 38 classical tyrosine-specific PTPs (protein tyrosine phosphatases). Many PTPs have been shown to regulate fundamental cellular processes and several are mutated in human diseases. We report that the product of the PTPN20 gene at the chromosome locus 10q11.2 is alternatively spliced to generate 16 possible variants of the classical human non-transmembrane PTP 20 (hPTPN20). One of these variants, hPTPN20a, was expressed in a wide range of both normal and transformed cell lines. The catalytic domain of hPTPN20 exhibited catalytic activity towards tyrosyl phosphorylated substrates, confirming that it is a bona fide PTP. In serum-starved COS1 cells, hPTPN20a was targeted to the nucleus and the microtubule network, colocalizing with the microtubule-organizing centre and intracellular membrane compartments, including the endoplasmic reticulum and the Golgi apparatus. Stimulation of cells with epidermal growth factor, osmotic shock, pervanadate, or integrin ligation targeted hPTPN20a to actin-rich structures that included membrane ruffles. The present study identifies hPTPN20a as a novel and widely expressed phosphatase with a dynamic subcellular distribution that is targeted to sites of actin polymerization.